Hydrated polyanion positive electrode material, preparation method and application
By preparing hydrated polyanionic cathode materials at room temperature, and utilizing the mixing and grinding of tartaric acid and vanadium-based oxalate phosphate to form a uniform sheet structure, the problems of conductivity and diffusion rate of magnesium battery cathode materials were solved, enabling low-energy-consumption and high-efficiency large-scale production and improving the electrochemical performance of the battery.
Patent Information
- Application Number
- CN202511477157.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-16
- Publication Date
- 2025-11-11
AI Technical Summary
Existing magnesium battery cathode materials suffer from poor electronic conductivity and low magnesium ion diffusion rate. Furthermore, existing preparation methods are energy-intensive and unsuitable for large-scale production, resulting in poor battery consistency.
Hydrated polyanionic cathode materials were prepared at room temperature by mixing and grinding tartaric acid and vanadium oxalate phosphate to form a uniform sheet structure. Ketjen black and PTFE were used as conductive agents and binders to reduce energy consumption and improve material consistency.
This achievement enables the low-energy preparation of highly consistent cathode materials, improving the electronic/ionic conductivity and discharge specific capacity of magnesium batteries, and increasing the energy density of the batteries.
Smart Images

Figure CN120933305A_ABST
Abstract
Description
Technical Field
[0001] This solution relates to the field of battery technology, specifically to a hydrated polyanionic cathode material, its preparation method, and its application. Background Technology
[0002] With the explosive growth of the electric vehicle and large-scale energy storage markets, the development of new rechargeable batteries with high safety, low cost, and high energy density has become a global strategic focus. Lithium resource shortages and price fluctuations have spurred research into alternative multivalent ion batteries, among which magnesium batteries stand out due to the high theoretical capacity (3833 mAh / cm³) of magnesium metal anodes. 3 Far exceeding lithium's 2046 mAh / cm³ 3 Magnesium batteries are widely recognized as one of the most promising next-generation energy storage systems due to their dendrite-free nature (enhancing safety), crustal abundance (2.9%, approximately 1000 times that of lithium), and environmental friendliness. However, the commercialization of magnesium batteries has long been hampered by the lack of high-performance cathode materials, necessitating the development of cathode material systems that combine high specific capacity, high operating voltage, fast ion conductivity, and long cycle life. Among existing cathode materials, polyanionic compounds stand out due to their stable framework structure and tunable voltage platform (via anionic groups such as PO4). 3- SiO4 4- Induction (IC) has become a research hotspot in recent years. However, its electronic conductivity is poor (<10). -10 The problems of low S / cm and low magnesium ion diffusion rate remain unresolved. Meanwhile, the preparation of polyanionic compounds often employs high-temperature solid-state methods and sol-gel methods, which involve high reaction temperatures and extremely high energy consumption, making large-scale preparation a major obstacle to their further development.
[0003] Currently, Chinese patent CN202311786628.4 discloses a method for preparing silicate cathode material MgFeSiO4 and its application. A simple and efficient electrojoule heating method can achieve rapid preparation of the target product. The resulting cathode material exhibits good cycle stability, but its discharge capacity is only 62.6 mAh / g, and the material has poor crystallinity. CN202410907661.6 discloses a composite magnesium pyrophosphate battery cathode material, its preparation method, and its application. This method improves voltage and initial capacity through composite coating and ion doping. The material is prepared using a high-temperature solid-state method, but its production cost is high, and its cycle performance is limited. Summary of the Invention
[0004] The present invention aims to provide a method for preparing a hydrated polyanionic cathode material, so as to provide a cathode material with high discharge capacity and low energy consumption in preparation.
[0005] To achieve the above objectives, the present invention adopts the following technical solution: a method for preparing a hydrated polyanionic cathode material, comprising the following steps: S1: Vanadyl oxalate phosphate and conductive agent are thoroughly mixed at a mass ratio of 7:2 to obtain a mixture; S2: Add an equal mass of binder to the mixture obtained in S1, mix the binder with the mixture, and press it to a suitable thickness to obtain the positive electrode material.
[0006] The advantages of this solution are as follows: Existing synthesis methods require long-term high-temperature and high-pressure reactions, consuming a large amount of energy and incurring high equipment investment and maintenance costs. Furthermore, existing synthesis methods are difficult to scale up for production. While parameters are easily controlled during small-scale laboratory synthesis, uneven temperature and pressure distribution within the reactor during industrial production can lead to variations in particle size distribution and crystallinity between different batches, affecting battery consistency. The cathode material obtained by this method is prepared entirely at room temperature, resulting in lower energy consumption. Simultaneously, it avoids the problem of uneven temperature and pressure distribution within the reactor causing variations in particle size distribution and crystallinity between different batches, leading to higher product consistency.
[0007] Furthermore, in S1, the preparation method of vanadium-based oxalate phosphate is as follows: Step 1: At room temperature, vanadium pentoxide, tartaric acid, and potassium hydroxide are mixed in distilled water with a molar ratio of 1.67 in a molar ratio of 1:(1~1.8):(2~5) to form a mixed solution; phosphoric acid with a molar ratio of 20 is diluted with deionized water to obtain a dilute phosphoric acid solution with a molar concentration of 14.29 mol / L. Step 2: Slowly add dilute phosphoric acid solution to the mixed solution while stirring continuously to obtain a blue-green precipitate of hydrate phase. Separate the precipitate and dry it to obtain vanadium-based oxalate phosphate.
[0008] This scheme utilizes tartaric acid to decompose and generate oxalate, which then complexes with vanadium ions. In this scheme, tartaric acid is not merely a common complexing agent; its unique molecular structure plays a crucial structural guiding role, which is impossible with traditional oxalic acid. This scheme replaces oxalic acid with tartaric acid to complete the production of the cathode material. Compared with oxalic acid, the only two carboxyl groups (-COOH) in the oxalic acid molecule can form bidentate ligands and form a five-membered ring, but its coordination ability and mode are relatively simple. At the same time, compared with tartaric acid, oxalic acid has a strong reducing agent and a relatively stronger ability to reduce vanadium ions. The reaction is more vigorous and prone to over-reduction, resulting in a complex valence state of vanadium ions in the product. This leads to low utilization of active material in the prepared cathode material and poor rate performance.
[0009] In addition, oxalic acid molecules have a simple structure, are linear and short, and have low steric hindrance. Although they can also guide the formation of structures, their template effect is weak, and they are prone to forming dense or highly disordered structures. Dense structures severely restrict the diffusion dynamics of magnesium ions, resulting in poor cycling stability. At the same time, dense or highly disordered structures are prone to irreversible phase transitions during cycling.
[0010] Furthermore, in step one, the mixing method is either magnetic stirring or mechanical stirring, and the stirring time is greater than or equal to ten minutes; in S2, the mixing method of vanadium-based oxalate phosphate and conductive agent is grinding and mixing; in S1, the mixing method of vanadium-based oxalate phosphate and conductive agent is grinding and mixing; in S2, the mixing method of mixture and binder is grinding and mixing.
[0011] Furthermore, in step two, the stirring time after adding the dilute phosphoric acid solution is greater than or equal to 12 hours.
[0012] Furthermore, in S2, the conductive agent is Ketjen Black, and the binder is PTFE.
[0013] A hydrated polyanionic cathode material comprises a mixture of vanadium-based oxalate phosphate, a conductive agent, and a binder in a mass ratio of 7:2:1, and the mixture is pressed into a uniform sheet with a thickness ranging from 100 μm to 0.5 mm.
[0014] Furthermore, during the mixing process, vanadium-based oxalate phosphate and conductive agent are first mixed evenly in a mass ratio of 7:2, and then mixed and ground with binder until they are in sheet form. Finally, they are pressed into uniform sheets with a thickness range of 100μm-0.5mm.
[0015] Furthermore, the conductive agent is Ketjen Black, and the binder is PTFE.
[0016] An application of a hydrated polyanionic cathode material in magnesium metal batteries involves cutting the cathode material and using it as the cathode sheet of the battery. The cathode material is formed by pressing a mixture of vanadium-based oxalate phosphate, a conductive agent, and a binder in a mass ratio of 7:2:1, resulting in a uniform sheet with a thickness ranging from 100 μm to 0.5 mm. Two mixing methods can be used to prepare this cathode material: one is to directly mix the vanadium-based oxalate phosphate, conductive agent, and binder in the above mass ratio and then press them into a uniform sheet with a thickness of 100 μm to 0.5 mm; the other is to first mix the vanadium-based oxalate phosphate and the conductive agent in a mass ratio of 7:2 uniformly, then mix and grind them with the binder to form a sheet, and finally press it into a uniform sheet with a thickness of 100 μm to 0.5 mm. Ketjen Black can be used as the conductive agent, and PTFE can be used as the binder.
[0017] Furthermore, the electrode is assembled with the electrolyte and metallic magnesium to form a magnesium metal battery. Attached Figure Description
[0018] Figure 1 This is a schematic diagram of the positive electrode material prepared according to an embodiment of the present invention; Figure 2 An electron micrograph of the cathode material prepared according to the present invention; Figure 3 This is a specific capacity diagram of the positive electrode material prepared in the embodiments of the present invention after being assembled into a button cell; Figure 4 This is a comparison between the XRD pattern of the cathode material prepared in this invention and the standard XRD pattern of a single crystal. Detailed Implementation
[0019] Example 1 Example 1 is basically as shown in the appendix. Figure 1-3 As shown, Figure 1-3 The invention relates to a hydrated polyanionic cathode material, its preparation method, and its application. The cathode material comprises a mixture of vanadium-based oxalate phosphate, a conductive agent, and a binder in a mass ratio of 7:2:1. Specifically, the conductive agent is Ketjen black, and the binder is PTFE. During mixing, the vanadium-based oxalate phosphate and Ketjen black in a mass ratio of 7:2 are first mixed evenly, and then mixed with PTFE and ground into a sheet shape. Finally, the sheet is pressed into a uniform sheet with a thickness ranging from 100 μm to 0.5 mm.
[0020] The preparation method is as follows: Step 1: At room temperature, vanadium pentoxide (Aldrich, 98%), tartaric acid (Merck, 99.5%), and potassium hydroxide (BDH, 99%) are mixed in distilled water with a molar ratio of 1.67 at a molar ratio of 1:(1~1.8):(2~5). The mixture is magnetically stirred for 10 minutes at room temperature to form a mixed solution. In this example, the molar ratio of vanadium pentoxide (Aldrich, 98%), tartaric acid (Merck, 99.5%), and potassium hydroxide (BDH, 99%) is 1:1.4:4. Subsequently, phosphoric acid (85%) with a molar ratio of 20 is diluted with deionized water to obtain a dilute phosphoric acid solution with a molar concentration of 14.29 mol / L. Step 2: Slowly add dilute phosphoric acid solution to the mixed solution and stir continuously for 12 hours to obtain a blue-green precipitate of hydrate phase. Separate the precipitate and dry it at room temperature for 24 hours to obtain the following... Figure 1 , Figure 2 The vanadium-based oxalate phosphate shown is (KVPC-1).
[0021] S1: Vanadyl oxalate phosphate and conductive agent (Ketjen Black) are thoroughly mixed and ground at a mass ratio of 7:2 to obtain a mixture; S2: Add an equal mass of binder (PTFE) to the mixture obtained in S1, and continue grinding until it becomes sheet-like to obtain a crude product. Then, roll the crude product into a uniform sheet with a thickness of (100um~0.5mm) to obtain the positive electrode material.
[0022] Battery assembly and testing: (1) Electrode preparation: The positive electrode material was cut into 0.6*0.6 cm pieces. 2 The electrode sheet is used as an electrode.
[0023] (2) Electrolyte preparation: Prepare a mixed electrolyte G4 of 0.3 mol / ml magnesium bis(trifluoromethanesulfonyl)imide (MT) and 0.6 mol / ml potassium bis(trifluoromethanesulfonyl)imide (KT). The preparation steps are as follows: (a) Weigh 0.417 g of MT and put it into a 5 ml sample bottle; (b) Add 1.88 ml of DME; (c) Add 0.5 ml of M4; (d) Stir magnetically for 5-8 min; (e) Add 0.456 g of KT; (f) Stir magnetically for 1 h until a clear electrolyte is obtained.
[0024] (3) Button battery assembly: The button battery was assembled using an electrode sheet as the positive electrode, G4 as the electrolyte, a magnesium sheet with a diameter of 14 mm as the negative electrode, and glass fiber as the separator to obtain a hydrated polyanion magnesium ion battery KVPC-1-G4.
[0025] (4) Battery test: The button cell KVPC-1-G4 was charged and discharged at a current density of 50mA / g and the charge and discharge capacity was tested. The test results are shown in Table 1.
[0026] Example 2 Example 2 is basically the same as Example 1, except that the molar ratio of vanadium pentoxide (Aldrich, 98%), tartaric acid (Merck, 99.5%) and potassium hydroxide (BDH, 99%) in the mixed solution is 1:1:2, thereby obtaining the positive electrode material. The button cell KVPC-1-G4 made with the positive electrode material was subjected to charge-discharge experiments at a current density of 50 mA / g and the charge-discharge capacity was tested. The test results are shown in Table 1.
[0027] Example 3 Example 2 is basically the same as Example 1, except that the molar ratio of vanadium pentoxide (Aldrich, 98%), tartaric acid (Merck, 99.5%) and potassium hydroxide (BDH, 99%) in the mixed solution is 1:1.8:5. The prepared button cell KVPC-1-G4 was subjected to charge-discharge experiments at a current density of 50 mA / g and the charge-discharge capacity was tested. The test results are shown in Table 1.
[0028] Comparative Example 1 First, 2 mmol V₂O₅ and 6 mmol oxalic acid were added to 50 mL of deionized water and stirred at 70 °C for 1 h to obtain a clear blue solution. Then, 12 mmol KH₂PO₄ was added to the solution, resulting in another blue solution. After stirring for another 10 min, the solution was transferred to an 80 mL polytetrafluoroethylene hydrothermal reactor and subjected to a hydrothermal reaction at 160 °C for 12 h to obtain a bright green precipitate. Finally, the precipitate was separated by centrifugation, washed three times with deionized water and ethanol, and dried at room temperature for 24 h to obtain the blue-green cathode material—vanadium-based oxalate phosphate (KVPC-2.1).
[0029] Subsequently, KVPC-2.1 and the conductive agent (Ketjen Black) were thoroughly mixed and ground at a mass ratio of 7:2. Then, an equal mass of binder (PTFE) was added, and grinding continued until a sheet was formed. The material was then rolled into a uniform sheet with a thickness of 100µm to 0.5mm, and finally cut into 0.6*0.6 cm pieces. 2 The electrode sheet is used as the positive electrode material.
[0030] Subsequently, button cell batteries were assembled using KVPC-2.1 as the positive electrode material, G4 as the electrolyte, a 14 mm diameter magnesium sheet as the negative electrode, and glass fiber as the separator, to obtain the hydrated polyanion magnesium ion battery KVPC-2.1-G4.
[0031] Finally, the button cell KVPC-2.1-G4 was subjected to charge-discharge experiments at a current density of 50 mA / g and a voltage range of 0.5–3.2V to test its charge-discharge capacity. The test results are shown in Table 1.
[0032] Comparative Example 2 First, vanadium pentoxide (Aldrich, 98%), tartaric acid (Merck, 99.5%), and potassium hydroxide (BDH, 99%) were mixed in distilled water at a molar ratio of 1:2:4 and magnetically stirred at room temperature for 10 min to form a mixed solution. Then, 30 moles of phosphoric acid (85%) were diluted with 40 ml of deionized water and slowly added to the solution while stirring continuously for 12 hours to obtain a blue-green precipitate of hydrate phase—vanadium-based oxalate phosphate (KVPC-2.2).
[0033] Subsequently, KVPC-2.2 was dried at room temperature for 24 hours, then thoroughly mixed and ground with a conductive agent (Ketjen Black) at a mass ratio of 7:2. A binder (PTFE) at a mass ratio of 1 was then added, and grinding continued until a sheet was formed. The material was then rolled into a uniform sheet with a thickness of 100µm to 0.5mm, and finally cut into 0.6*0.6 cm pieces. 2 The electrode sheet is used as the positive electrode material.
[0034] Subsequently, using KVPC-2.2 as the positive electrode material, G4 as the electrolyte, a 14 mm diameter magnesium sheet as the negative electrode, and glass fiber as the separator, a button cell was assembled to obtain the hydrated polyanion magnesium ion battery KVPC-3-G4.
[0035] Finally, the button cell KVPC-3-G4 was subjected to charge-discharge experiments at a current density of 50 mA / g and a voltage range of 0.5–3.2V to test its charge-discharge capacity. The test results are shown in Table 1.
[0036] Comparative Example 3 Comparative Example 3 was essentially the same as Comparative Example 1, except that the molar ratio of vanadium pentoxide (Aldrich, 98%), tartaric acid (Merck, 99.5%), and potassium hydroxide (BDH, 99%) in the mixed solution was 1:0.9:4. Vanadyl oxalate phosphate (KVPC-2.3) was obtained from this mixed solution. Subsequently, the obtained vanadium oxalate phosphate (KVPC-2.3) was dried for 24 hours and then thoroughly mixed and ground with a conductive agent (Ketjen Black) at a mass ratio of 7:2. Then, a binder (PTFE) at a mass ratio of 1 was added, and grinding continued until a sheet was formed. The material was rolled into a uniform sheet with a thickness of (100 μm ~ 0.5 mm) using a rolling mill method, and finally cut into 0.6 * 0.6 cm pieces. 2 The electrode sheet is used as the positive electrode material.
[0037] Subsequently, button cell batteries were assembled using KVPC-2.3 as the positive electrode material, G4 as the electrolyte, a 14 mm diameter magnesium sheet as the negative electrode, and glass fiber as the separator, to obtain the hydrated polyanion magnesium ion battery KVPC-2.3-G4.
[0038] Finally, the button cell KVPC-2.3-G4 was subjected to charge-discharge experiments at a current density of 50 mA / g and a voltage range of 0.5 to 3.2V to test its charge-discharge capacity. The test results are shown in Table 1.
[0039] Comparative Example 4 Comparative Example 4 was essentially the same as Example 1, except that, under reaction conditions of 80°C, tartaric acid in the mixed solution was replaced with iminodiacetic acid to synthesize vanadium-based oxalate phosphate (KVPC-2.4). Subsequently, the obtained vanadium-based oxalate phosphate was dried for 24 hours and then thoroughly mixed and ground with a conductive agent (Ketjen Black) at a mass ratio of 7:2. A binder (PTFE) at a mass ratio of 1 was then added, and grinding continued until a sheet was formed. The material was rolled into a uniform sheet with a thickness of (100 μm ~ 0.5 mm) using a rolling mill method, and finally cut into 0.6 * 0.6 cm pieces. 2 The electrode sheet is used as the positive electrode material.
[0040] Subsequently, button cells were assembled using KVPC-2.4 as the positive electrode material, G4 as the electrolyte, a 14 mm diameter magnesium sheet as the negative electrode, and glass fiber as the separator, to obtain the hydrated polyanion magnesium ion battery KVPC-2.4-G4.
[0041] Finally, the button cell KVPC-2.4-G4 was subjected to charge-discharge experiments at a current density of 50mA / g and a voltage range of 0.5 to 3.2V to test its charge-discharge capacity. The test results are shown in Table 1.
[0042] Comparative Example 5 Comparative Example 5 is essentially the same as Example 1, except that the molar ratio of potassium hydroxide to vanadium pentoxide in the mixed solution is 1. Vanadyl oxalate phosphate (KVPC-2.5) is obtained from this mixed solution. Subsequently, the obtained vanadium oxalate phosphate (KVPC-2.5) is dried for 24 hours and then thoroughly mixed and ground with a conductive agent (Ketjen Black) at a mass ratio of 7:2. Then, a binder (PTFE) at a mass ratio of 1 is added, and grinding continues until a sheet is formed. The material is rolled into a uniform sheet with a thickness of (100 μm ~ 0.5 mm) using a rolling method, and finally cut into 0.6 * 0.6 cm pieces. 2 The electrode sheet is used as the positive electrode material.
[0043] Subsequently, button cell batteries were assembled using KVPC-2.5 as the positive electrode material, G4 as the electrolyte, a 14 mm diameter magnesium sheet as the negative electrode, and glass fiber as the separator, to obtain the hydrated polyanion magnesium ion battery KVPC-2.5-G4.
[0044] Finally, the button cell KVPC-2.5-G4 was subjected to charge-discharge experiments at a current density of 50 mA / g and a voltage range of 0.5 to 3.2V to test its charge-discharge capacity. The test results are shown in Table 1.
[0045] Comparative Example 6 Comparative Example 6 is essentially the same as Example 1, except that the molar ratio of potassium hydroxide to vanadium pentoxide in the mixed solution is 6. Vanadyl oxalate phosphate (KVPC-2.6) is obtained from this mixed solution. Subsequently, the obtained vanadium oxalate phosphate (KVPC-2.6) is dried for 24 hours and then thoroughly mixed and ground with a conductive agent (Ketjen Black) at a mass ratio of 7:2. Then, a binder (PTFE) at a mass ratio of 1 is added, and grinding continues until a sheet is formed. The material is rolled into a uniform sheet with a thickness of (100 μm ~ 0.5 mm) using a rolling method, and finally cut into 0.6 * 0.6 cm pieces. 2 The electrode sheet is used as the positive electrode material.
[0046] Subsequently, button cell batteries were assembled using KVPC-2.6 as the positive electrode material, G4 as the electrolyte, a 14 mm diameter magnesium sheet as the negative electrode, and glass fiber as the separator, to obtain the hydrated polyanion magnesium ion battery KVPC-2.6-G4.
[0047] Finally, the button cell KVPC-2.6-G4 was subjected to charge-discharge experiments at a current density of 50 mA / g and a voltage range of 0.5 to 3.2V to test its charge-discharge capacity. The test results are shown in Table 1.
[0048] Table 1
[0049] In summary, this method allows for precise control of the reaction chelation environment by adjusting the ratio of tartaric acid and alkali, enabling room-temperature-scale synthesis of this material and significantly reducing the preparation cost of polyanionic cathode materials. The reaction requires no external driving force, and the drying process does not require high-temperature equipment, further reducing production costs.
[0050] In this reaction, tartaric acid ligands can decompose in situ into oxalic acid, forming an oxalate phosphate framework that provides open ion diffusion channels, promoting the formation of the hydrated phase. In the hydrated phase, water molecules shield Mg... 2+ High charge density lowers the desolvation energy barrier; simultaneously, it forms a "water-lubricated layer," expanding ion migration channels to accommodate larger Mg atoms. 2+ (0.72 Å), to alleviate structural stress during magnesium ion insertion / extraction.
[0051] The synthesized cathode material with a sheet-like morphology and a particle size in the range of 100nm-2μm has high electronic / ionic conductivity and high tap density, and can release a high discharge specific capacity of 117mAh / g, which is beneficial to improving the energy density of magnesium-based batteries.
[0052] The above descriptions are merely embodiments of the present invention, and common knowledge such as specific technical solutions and / or characteristics are not described in detail here. It should be noted that the technical means for solving problems in the above embodiments of the present invention can be used in combination to solve multiple technical problems simultaneously. For those skilled in the art, several modifications and improvements can be made without departing from the technical solutions of the present invention, and these should also be considered within the scope of protection of the present invention. These modifications and improvements will not affect the effectiveness of the implementation of the present invention or the practicality of the patent. The scope of protection claimed in this application should be determined by the content of its claims, and the specific embodiments described in the specification can be used to interpret the content of the claims.
Claims
1. A method for preparing a hydrated polyanionic cathode material, characterized in that: Includes the following steps: S1: Vanadyl oxalate phosphate and conductive agent are thoroughly mixed at a mass ratio of 7:2 to obtain a mixture; S2: Add an equal mass of binder to the mixture obtained in S1, mix the binder with the mixture, and press it into a uniform sheet with a thickness ranging from 100μm to 0.5mm to obtain the positive electrode material; In S1, the preparation method of vanadium-based oxalate phosphate is as follows: Step 1: At room temperature, vanadium pentoxide, tartaric acid, and potassium hydroxide are mixed in distilled water with a molar ratio of 1.67 in a molar ratio of 1:(1~1.8):(2~5) to form a mixed solution; phosphoric acid with a molar ratio of 20 is diluted with deionized water to obtain a dilute phosphoric acid solution with a molar concentration of 14.29 mol / L. Step 2: Slowly add dilute phosphoric acid solution to the mixed solution while stirring continuously to obtain a blue-green precipitate of hydrate phase. Separate the precipitate and dry it to obtain vanadium-based oxalate phosphate.
2. The method for preparing a hydrated polyanionic cathode material according to claim 1, characterized in that: In step one, the mixing method is either magnetic stirring or mechanical stirring, and the stirring time is greater than or equal to ten minutes; in S1, the mixing method of vanadium-based oxalate phosphate and conductive agent is grinding and mixing; in S2, the mixing method of mixture and binder is grinding and mixing.
3. The method for preparing a hydrated polyanionic cathode material according to claim 1, characterized in that: In step two, the stirring time after adding the dilute phosphoric acid solution is greater than or equal to 12 hours.
4. The method for preparing a hydrated polyanionic cathode material according to claim 1, characterized in that: In S2, the conductive agent is Ketjen Black and the binder is PTFE.
5. A hydrated polyanionic cathode material, characterized in that: The mixture comprises vanadium-based oxalate phosphate, conductive agent and binder in a mass ratio of 7:2:1, and the mixture is pressed into uniform sheets with a thickness ranging from 100μm to 0.5mm.
6. The hydrated polyanionic cathode material according to claim 5, characterized in that: During mixing, vanadium-based oxalate phosphate and conductive agent are first mixed evenly in a mass ratio of 7:2, then mixed with binder and ground into a sheet, and finally pressed into a uniform sheet with a thickness range of 100μm-0.5mm.
7. The hydrated polyanionic cathode material according to claim 5, characterized in that: The conductive agent is Ketjen Black, and the binder is PTFE.
8. An application of a hydrated polyanionic cathode material, characterized in that: The positive electrode material described in any one of claims 5-7 is cut and used as the electrode sheet of the positive electrode of the battery.
9. The application of the hydrated polyanionic cathode material according to claim 8, characterized in that: Electrodes are assembled with electrolyte and magnesium metal to form a magnesium metal battery.
Citation Information
Patent Citations
Preparation method and application of silicate positive electrode material MgFeSiO4
CN117776192A
Composite pyrophosphate magnesium battery positive electrode material and preparation method and application thereof
CN118782776A
Potassium ion battery high-potential positive electrode material and preparation method thereof
CN110467170A
Preparation method and application of carbon-coated KVPO4F porous nanosheet
CN114956032A
Hybrid polyanion vanadium-based positive electrode material, preparation method thereof and sodium ion battery
CN118156495A